Strategi Public Relations Radio FM Pasuruan dalam Meningkatkan Daya Saing Radio di Era Media Digital - Aziz, Abdul; Muyasaroh, Siti (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
This research aims to examine the Public Relations strategies implemented by Radio Star 105.5 FM Pasuruan in enhancing competitiveness in the digital media era. The study adopts a qualitative descriptive method, with data collected through in-depth interviews, direct observation, and documentation. The research informants include the Public Relations team, broadcasters, and the management of Radio Star FM. The data were analyzed thematically to identify patterns in the PR strategies applied.The findings indicate that Radio Star FM applies five main strategies: (1) maximizing the use of social media to foster interactive communication and reach younger audiences; (2) expanding broadcast coverage through internet-based streaming services; (3) implementing two-way communication with listeners through quizzes, live broadcasts, and polls; (4) continuously innovating broadcast content to align with trends and audience needs; and (5) integrating conventional